Antibiofilm activity and mode of action of DMSO alone and its combination with afatinib against Gram-negative pathogens - Yahya, Mohd Fakharul Zaman Raja; Alias, Zazali; Karsani, Saiful Anuar (Springer Verlag, 2018)
Biofilms are complex microbial communities that tend to attach to either biotic or abiotic surface. Enclosed in a self-produced extracellular polymeric substance (EPS) matrix, the biofilms often cause persistent infections. The objective of this study was to investigate the antibiofilm activity of dimethyl sulfoxide (DMSO) and afatinib against Gram-negative pathogens. Test microorganisms used in this study were Escherichia coli ATCC 1299, Pseudomonas aeruginosa ATCC 10145, and Salmonella typhimurium ATCC 14028. Biofilms were developed in 96-well microplate at 37°C for 24 h. Following removal of non-adherent cells, analysis of biofilm viability, biofilm biomass, and extracellular polymeric substances (EPS) matrix were performed using resazurin assay, crystal violet assay, and attenuated total reflectance fourier transform infrared (ATR-FTIR) spectroscopy, respectively. Bradford protein assay was conducted to determine the total amount of EPS proteins. The results demonstrated that both 32% DMSO alone and its combination with 3.2 μg/mL afatinib were effective in killing biofilm cells and reducing biofilm biomass. IR spectral variations of EPS matrix of biofilms in the range between 1700 and 900 cm−1 were also observed. Reduction in EPS proteins verified the chemical modifications of EPS matrix. In conclusion, 32% DMSO alone and its combination with 3.2 μg/mL afatinib showed remarkable antibiofilm activities against Gram-negative pathogens. It was suggested that the biofilm inhibition was mediated by the chemical modification of EPS matrix.